Small and Medium Enterprise (SME) Innovation and Creativity in a Pandemic - Dhanar Dhono Vernandhie (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study is to find out 1) which SME in Pringsewu Regency can survive in the midst of the Covid-19 pandemic; 2) how are the innovations and creativity carried out by SME in Pringsewu Regency so that they can survive in the midst of the Covid-19 pandemic. The method used in this research is descriptive qualitative. The subjects in this study were 30 SME in Pringsewu Regency. The study was conducted on March 1 to March 30, 2021. The results of the study concluded that of the 30 SME in Pringsewu, there were 7 SME that were unable to survive and the rest were still trying to survive. This is because apart from the Covid-19 outbreak, these entrepreneurs do have constraints in capital, processing of production materials and sales, which are made worse during the pandemic. In terms of innovation and creativity, things that have been done include moving the way of selling from offline to online during the pandemic, creating a new product that is truly unique, modifying products that create new qualities and styles to increase sales